Dynamics of Mammary Epithelial Cell Differentiation. "What's SLUG Got to Do With It?". - Phillips, Sarah. (2017)
Abstract: Perturbations in stem cell activity and differentiation can lead to developmental defects and cancer. How mutations in genes affect these processes are difficult to study in mammals, and often require the creation of transgenic mice. Here, I use a novel approach involving a quantitative model of cell-state transitions in vitro to gain insights into how SLUG/SNAI2, a key developmental transcription factor, modulates mammary epithelial stem cell activity and differentiation in vivo. In the absence of SLUG, stem cells fail to transition into basal progenitor cells, while existing basal progenitor cells undergo luminal differentiation. Disruption of basal cell-state transitions is offset by the proliferation and expansion of luminal progenitor cells; together these changes result in abnormal mammary architecture and defects in tissue function. Furthermore, we show that in the absence of SLUG, mammary stem cell activity necessary for tissue regeneration following transplantation and for cancer initiation are lost. Mechanistically, SLUG regulates differentiation and cellular plasticity by recruiting the chromatin modifier, LSD1 (Lysine specific demethylase 1), to promoters of lineage-specific genes to repress transcription. Together, these results reveal the complex connection between stem cell dynamics and cellular differentiation, and demonstrate that SLUG plays a dual role in repressing luminal epithelial differentiation while unlocking stem cell transitions necessary for tumorigenesis.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Genetics.; Advisor: Charlotte Kuperwasser.; Committee: Grace Gill, Philip Hinds, and James Schwob.; Keywords: Molecular biology, and Cellular biology.